2022
DOI: 10.20525/ijrbs.v11i8.2121
|View full text |Cite
|
Sign up to set email alerts
|

Why HR, corporate and marketing communication divisions should work together?

Abstract: The aim of this study is to find out what factors can increase employer branding and job pursuit intentions from one of the banks in Indonesia. The data in this study were distributed to 114 respondents and evaluated using the PLS-SEM analysis technique. This study found no effect between product brand and job pursuit intention, but this effect changed when using employer branding. Meanwhile, the corporate brand was found to affect job pursuit intention either through employer branding or not. This study propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…After the indicator items have been evaluated for convergent validity, the next step is to evaluate the reliability of each latent variable using Cronbach's alpha and the composite reliability of both rho_a and rho_c. This study obtained results showing the high reliability of each latent variable; this is shown in Table 3, where each variable has a Cronbach's alpha value above 0.60 and a composite reliability value for both rho_a and rho_c above 0.70 (Rinaldi & Putra, 2022).…”
Section: Results and Discussion Resultsmentioning
confidence: 84%
“…After the indicator items have been evaluated for convergent validity, the next step is to evaluate the reliability of each latent variable using Cronbach's alpha and the composite reliability of both rho_a and rho_c. This study obtained results showing the high reliability of each latent variable; this is shown in Table 3, where each variable has a Cronbach's alpha value above 0.60 and a composite reliability value for both rho_a and rho_c above 0.70 (Rinaldi & Putra, 2022).…”
Section: Results and Discussion Resultsmentioning
confidence: 84%
“…Evaluation of the measurement model or outer model is carried out to assess the validity and reliability of the model. The research measurement model in PLS-SEM is the outer model, which consists of a set of relationships between indicators and latent variables (Andriani & Putra, 2019;Fahmi, Kostini et al, 2022;Fahmi, Novel et al, 2022;Putra, 2022;Putra & Ardianto, 2022;Rinaldi & Putra, 2022). According to Hair et al (2018), to assess convergent validity, namely, the loading factor value must be more than 0.70.…”
Section: Findings and Discussionmentioning
confidence: 99%